Moisture origins of the Amazon carbon source region. (1st April 2023) - Staal, Arie; Koren, Gerbrand; Tejada, Graciela; Gatti, Luciana V
Abstract: The southeastern Amazon has recently been shown to be a net carbon source, which is partly caused by drying conditions. Drying depends on a number of factors, one of which is the land cover at the locations where the moisture has originated as evaporation. Here we assess for the first time the origins of the moisture that precipitates in the Amazon carbon source region, using output from a Lagrangian atmospheric moisture tracking model. We relate vegetation productivity in the Amazon carbon source region to precipitation patterns and derive land-cover data at the moisture origins of these areas, allowing us to estimate how the carbon cycle and hydrological cycle are linked in this critical part of the Amazon. We find that, annually, 13% of the precipitation in the Amazon carbon source region has evaporated from that same area, which is half of its land-derived moisture. We further find a moisture-recycling-mediated increase in gross primary productivity of roughly 41 Mg carbon km −2 yr −1 within the Amazon carbon source region if it is fully forested compared to any other land cover. Our results indicate that the parts of the Amazon forest that are already a net carbon source, still help sustain their own biomass production. Although the most degraded parts of the Amazon depend mostly on oceanic input of moisture, further degradation of this region would amplify carbon losses to the atmosphere.